Emergency Lumbar Puncture in Adults - Macdonald, R. Loughlin (1989)
Three patients who had lumbar punctures performed in the presence of undiagnosed intracranial space-occupying lesions are described. Neurologic deterioration was precipitated in one and continued in another; neurologic status was unchanged in the third patient. The use of lumbar puncture in adults in the emergency setting is discussed in light of the accepted indications and contra-indications, available data on complication rates, and regional availability of cranial computed tomography. We recommend that all patients undergo computed tomography or other brain imaging, such as magnetic resonance, prior to lumbar puncture in order to detect unsuspected intracranial mass lesions or other abnormalities (such as subarachnoid hemorrhage and hydrocephalus) that would preclude lumbar puncture.